2021
DOI: 10.1016/j.jtauto.2021.100085
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence that mycobacteria are associated with the pathogenesis of Sjogren’s syndrome?

Abstract: Sjogren’s syndrome (SS) is a common, systemic autoimmune disorder primarily affecting the exocrine glands resulting in xerostomia and xerophthalmia. SS may also manifest with polyarthralgia, polyarthritis, polymyalgia, cutaneous/other organ vasculitis, interstitial lung disease, and/or various other disorders. The primary autoantibodies associated with SS and used as adjuncts to diagnosis are anti-Ro (SSA) and anti-La (SSB). The pathogenesis of SS is considered to involve genetic susceptibility and environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…It has been reported that exposure to mycobacteria may be related to the pathogenesis of SS; thus, it is hypothesized that the bacilli Calmette-Guerin (BCG) vaccine and antimycobacterial drugs may contribute to the prevention and treatment of SS. 9 According to Chao et al, a correlation exists between NTM infection and SS, and this correlation is very high in postmenopausal and nonbronchiectasis subjects. 10 The mechanism of this correlation may be related to type I interferon and sex hormones.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that exposure to mycobacteria may be related to the pathogenesis of SS; thus, it is hypothesized that the bacilli Calmette-Guerin (BCG) vaccine and antimycobacterial drugs may contribute to the prevention and treatment of SS. 9 According to Chao et al, a correlation exists between NTM infection and SS, and this correlation is very high in postmenopausal and nonbronchiectasis subjects. 10 The mechanism of this correlation may be related to type I interferon and sex hormones.…”
Section: Discussionmentioning
confidence: 98%
“…To date, MAP has been causally associated with granulomatous diseases: Crohn’s (Kuenstner et al 2017 ), sarcoidosis (Celler BG 2018 ; Reid and Chiodini 1993 ) and Blau syndrome (Dow and Ellingson 2010 ). Through molecular mimicry from mycobacterial heat shock protein (hsp65) (Dow 2012 ), MAP induces autoantibodies in autoimmune diabetes (T1D) (Naser et al 2013 Jun), multiple sclerosis (Cossu et al 2013 ; Ekundayo et al 2022 ), autoimmune thyroiditis (Sisto et al 2010 ), lupus (Dow 2016 ), rheumatoid arthritis (Bo et al 2019a , 2018 ) and possibly, Sjogren’s syndrome (Dow and Chan 2021 ). The causal association of three diseases will be further featured: T1D, multiple sclerosis and rheumatoid arthritis.…”
Section: Johne’s Disease—paratuberculosis Of Animalsmentioning
confidence: 99%
“…Dow and Chan [ 88 ] recently reported that BCG has shown benefit in T1D mellitus and multiple sclerosis, autoimmune diseases that have been linked to MAP via Hsp65 and disease-specific autoantibodies. Obviously, a number of factors lend credence to the notion of a pathogenic link between environmental mycobacteria and Sjogren’s syndrome (SS), including the presence of antibodies to mycobacterial Hsp65 in SS, the homology of Hsp65 with SS autoantigens, and the beneficial effects seen with BCG vaccination against certain autoimmune diseases.…”
Section: Epitopes Proteins and Genes Of Nontuberculous Mycobacteria A...mentioning
confidence: 99%
“…Obviously, a number of factors lend credence to the notion of a pathogenic link between environmental mycobacteria and Sjogren’s syndrome (SS), including the presence of antibodies to mycobacterial Hsp65 in SS, the homology of Hsp65 with SS autoantigens, and the beneficial effects seen with BCG vaccination against certain autoimmune diseases. Furthermore, given that BCG may protect against NTM, has immune modifying effects, and has a strong safety record of billions of doses given, BCG and/or antimycobacterial therapeutics should be studied in SS [ 88 ].…”
Section: Epitopes Proteins and Genes Of Nontuberculous Mycobacteria A...mentioning
confidence: 99%